(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Alcoholic fermentation is a crucial process of making a drink. Honey wine differs from other alcoholic beverages by its specific honey aroma and taste, the organoleptic properties of which determine the quality of the product. Honey wine contains volatile components along with other substances: ethers and higher alcohols, which differ from each other in their organoleptic properties and can have different effects on the taste and aroma of the product. Higher alcohols are derived from amino acids in various ways (derived from raw materials, as well as obtained by chemical and biochemical transformations of various substances); the amino acid tyrosine is converted during the alcoholic fermentation process to form the aromatic alcohol tyrosol. The latter is characterized by the smell of honey and candle. Based on the above, we aimed to study tyrosol in our research facilities. To determine the dynamics of the accumulation of higher alcohol-tyrosol in the process of alcoholic fermentation of honey sweet, we used: paper chromatographic method for qualitative analysis, and spectrophotometric method for tyrosol quantification. It has been found that the most abundant alcohol with the smell and taste of honey - tyrosol, is present in small amounts in honey and is found in relatively large quantities in the product obtained from its alcoholic fermentation - honey wine.